A Fuzzy Rule-Based Expert System for Evaluating Intellectual Capital. (18th December 2012) - Zarandi, Mohammad Hossein Fazel; Mohammadhasan, Neda; Bastani, Susan
Abstract : A fuzzy rule-based expert system is developed for evaluating intellectual capital. A fuzzy linguistic approach assists managers to understand and evaluate the level of each intellectual capital item. The proposed fuzzy rule-based expert system applies fuzzy linguistic variables to express the level of qualitative evaluation and criteria of experts. Feasibility of the proposed model is demonstrated by the result of intellectual capital performance evaluation for a sample company.